Enhancement in mineral bioavailability of extruded pulses with reduced antinutrients. Issue 11 (24th October 2019) - Yadav, Neelam; Kaur, Devinder; Malaviya, Ritika; Saini, Pinki; Anjum, Saba
Abstract : Purpose: Iron deficiency anaemia and zinc deficiency are major public health problems across the globe. Cereals and pulses are important vegetarian source of minerals like zinc (Zn) and iron (Fe), however, poor digestibility impairs proper availability of micro minerals in the body. Chickpea ( Cicer arietinum L.) and cowpea ( Vigna unguiculata L. Walp) were selected for study as they are important pulse crops consumed worldwide. Therefore, in order to remove antinutrients and enhance bioavailability of nutrients in chickpea and cowpea, extrusion cooking was selected as a technology and its impact was studied by an in vitro method. The paper aims to discuss this issue. Design/methodology/approach: Four chickpea cultivars, two desi (K 850 and PUSA 362) and two kabuli (PUSA 1108 and PUSA 1053) and one cowpea (Gomati) cultivars were selected for the study. Pulses were processed in a laboratory using a single screw food extruder. Raw and extruded pulses were analysed for antinutrients content, micronutrients content (Fe, Zn) and their bioavailability. Findings: Extrusion cooking significantly decreased phytate in all cultivars of chick pea and cowpea with highest reduction (72.92 per cent) in PUSA 362; similarly, tannin and trypsin inhibitor decreased by 87.5 and 71.54 per cent, respectively, in Gomati cultivar of cowpea. All cultivars showed significant increase in protein digestibility. Iron bioavailability in all samples enhanced significantly; however, only 50 per cent cultivars (K 850, PUSA 362 and PUSA 1108) showed improvement in Zn bioavailability. Originality/value: The present research therefore brought the outcome as an enhanced in vitro protein digestibility and bioavailability of micro mineral and protein in certain pulses having minimized antinutrients. Therefore, it is concluded that extrusion cooking is an effective tool in enhancing protein and micro mineral bioavailability.